Recurrent exercise-induced rhabdomyolysis due to low intensity fitness exercise in a healthy young patient - Karre, Premnath Reddy (BMJ Publishing Group, 2011)
Rhabdomyolysis is an uncommon but life threatening condition that develops due to breakdown of muscle and release of intracellular components into the circulation. A 24-year-old man otherwise healthy was admitted to our hospital because of muscle aches and weakness as well as cola coloured urine developed 3 days after carrying out the low intensity exercise. Diagnosis of rhabdomyolysis was made with creatine kinase (CK) levels of 214 356 U/l. He was treated for a similar condition at age 21. A muscle biopsy was done and the findings were normal. Rhabdomyolysis can develop with low intensity exercise; thus, it be considered in healthy young people. Young people with recurrent rhabdomyolysis due to low intensity exercise, in the absence of obvious medical and physical causes, should be evaluated further to rule out uncommon metabolic diseases. Our case demonstrates that complications especially renal failure in patients with rhabdomyolysis do not correspond to CK levels.